Insecticidal potential of entomopathogenic nematodes of Northern Kazakhstan - Shibaeva, A.K.; Shaikhutdinov, V.M.; Myrzabayev, B.M. (Fundamental and Experimental Biology, 2022)
The goal of this research experiment is to create a biological preparation based on predatory nematodes to control potato pests. 15 isolates of entomopathogenic nematodes were isolated: 13 were isolated from coniferous and mixed forests; 2 from soils of agricultural fields: 1 from a potato field, 1 from a field sown with perennial grasses. Nematodes were identified as Steinernematids based on the color of the corpses of larvae of Galleria mellonella and the morphology of males. Isolates of entomopathogenic nematodes from various habitats (forests, agricultural fields, grasslands) of Akmola and Pavlodar regions were isolated. Screening of isolates on the larvae of the seed nutcracker (Agriotes obscurus) was carried out. It is stablished that the wireworm is sensitive to all isolates. Of the 15 isolates tested, 12 of these isolates showed high mortality ability in relation to wireworm: about 50–70 % mortality in laboratory biotests; 3 isolates (AF 15, AF 22, and AS 36) could not cause more than 40 % of the average mortality of larvae. The screening results showed that the isolates AF 29, AF57, and KP76 are good isolates for further studies as a possible bioinsecticide agent against A. obscurus.